A Parallel Multi-Deque Sorting Algorithm - Surin Kittitornkun; Apisit Rattanatranurak (My University, 2021)
Parallel or multithreaded sorting algorithms have been proposed and researched for multicore and manycore CPU and GPU systems. Some of them are based on divide and conquer concept to exploit data parallelism as well as task parallelism at the same time. In this paper, a Multi-Deque Sort (MDQSort) is proposed and developed on top of our previous algorithm called Multi-Stack (MSP) Sort. Therefore, the MDQSort can easily enhance the performance while getting rid of weaknesses of MSPSort. As a result, MDQSort can be as competitive as the Standard Template Library parallel mode sorting algorithms on a 4-core ARM Cortex A72 Linux system in terms of run time, stability, CPU utilization and memory (RAM) utilization.
Keywords: Algorithms and Data Compression; Parallel Computing and Optimization Techniques; Advanced Data Storage Technologies